Disutility Study for Adult Patients with Moderate to Severe Crohn’s Disease - Melany Worbes-Cerezo; Beenish Nafees; Andrew Lloyd; Katy Gallop; Imran Ladha; Cicely Kerr (Journal of Health Economics and Outcomes Research)
**Background:** Crohn’s disease (CD) treatments and associated adverse events (AEs) can be burdensome for patients. However, specific values which quantify the impact on health-related quality of life (HRQL) for economic evaluation are lacking.